2019
DOI: 10.1161/jaha.118.010541
|View full text |Cite
|
Sign up to set email alerts
|

Association of Major Adverse Cardiac Events up to 5 Years in Patients With Chest Pain Without Significant Coronary Artery Disease in the Korean Population

Abstract: Background Significant coronary artery disease has a well‐known association with long‐term adverse cardiovascular events. In this study, we aimed to evaluate its association with long‐term major adverse clinical events ( MACE ) up to 5 years in patients who presented with chest pain without significant coronary artery disease . Methods and Results A total of 5890 subjects with chest pain without significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 17 publications
1
42
1
1
Order By: Relevance
“…On day 31, following discharge from hospital, study physicians made calls to subjects/family members to record any MACE during the past 30 days. A MACE was defined as all-cause death, non-fatal myocardial infarction, or a revascularization procedure including Percutaneous coronary intervention (PCI) or Cronary artery bypass grafting (CABG) [ 27 ]. Similar to a previously published study, if more than one MACE occurred during the follow-up period, the most severe endpoint (all-cause death > myocardial infarction > revascularization) was selected for the 30-day MACE analysis [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…On day 31, following discharge from hospital, study physicians made calls to subjects/family members to record any MACE during the past 30 days. A MACE was defined as all-cause death, non-fatal myocardial infarction, or a revascularization procedure including Percutaneous coronary intervention (PCI) or Cronary artery bypass grafting (CABG) [ 27 ]. Similar to a previously published study, if more than one MACE occurred during the follow-up period, the most severe endpoint (all-cause death > myocardial infarction > revascularization) was selected for the 30-day MACE analysis [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the reduction of those CV risk factors is expected to be followed by the reduction of Major Adverse Cardiovascular Events (MACE; i.e., composites of CV death, myocardial infarction (MI), stroke, coronary revascularization or hospitalization for HF [11,12]). However, recent studies showed conflicting results, suggesting that obesity might provide better CV outcomes in specific populations (i.e., "obesity paradox") [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the reduction of those CV risk factors is expected to be followed by the reduction of Major Adverse Cardiovascular Events (MACE; i.e., composite of CV death, myocardial infarction [MI], stroke, coronary revascularization or hospitalization for HF (8,9)). However, recent studies showed conflicting results, suggesting that obesity might provide better CV outcomes in specific populations (i.e., "obesity paradox") (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the benefits of bariatric surgery in patients with obesity, including the improvements of body fat distribution and CV risk factors such as dyslipidemia, (pre)hypertension, insulin resistance, (pre)diabetes, non-alcoholic fatty liver disease, inflammation, vascular reactivity and obstructive sleep apnea (6). Typically, the reduction of those CV risk factors is expected to be followed by the reduction of Major Adverse Cardiovascular Events (MACE; i.e., composite of CV death, myocardial infarction [MI], stroke, coronary revascularization or hospitalization for HF (8, 9)). However, recent studies showed conflicting results, suggesting that obesity might provide better CV outcomes in specific populations (i.e., “obesity paradox”) (10-12).…”
Section: Introductionmentioning
confidence: 99%